Deforestation in the Amazon and macroeconomic variables: evidence from time-series analysis (2000–2023) - Vinícios Carvalho, Leandro; Gonçalves da Silva, Jonathan; Bonfim de Almeida, Roselaine (Sustainability in Debate, 2026)
Building on the premise that macroeconomic variables – such as prices, agricultural income, and the real exchange rate – are associated with deforestation dynamics, this study investigates both the longrun relationship between these variables and deforestation, as well as the effects of macroeconomic shocks on its temporal evolution. The empirical strategy is grounded in a time-series framework using annual data from 2000 to 2023 and employs unit root tests, the Johansen cointegration approach, and a Vector Error Correction Model (VECM). The results provide evidence of cointegration among the variables, indicating the existence of a long-run equilibrium relationship between macroeconomic conditions and deforestation. Granger causality tests underscore the predictive relevance of the real exchange rate within the system, particularly in relation to deforestation and agricultural variables. Variance decomposition analysis reveals that exchange rate shocks account for a substantial share of the fluctuations in deforestation, whereas agricultural prices and agricultural GDP contribute to a lesser extent. Furthermore, impulse–response functions indicate that positive shocks in prices and the real exchange rate generate positive cumulative effects on deforestation over time. These findings suggest that external competitiveness and the profitability of agricultural activities constitute key economic drivers of land-use expansion in the Amazon. At the same time, the results highlight the importance of the institutional environment, as conservation policies and monitoring mechanisms may mitigate the environmental pressures associated with favourable macroeconomic conditions. Overall, this study contributes to the literature by emphasising the interaction between macroeconomic dynamics and environmental outcomes in the Amazon region.